PENGARUH SUPERVISI, DISIPLIN DAN MOTIVASI TERHADAP PENINGKATAN KINERJA GURU SMK MUHAMMADIYAH WONOMULYO KABUPATEN POLEWALI MANDAR - Nursahdi Saleh (Siddiq Institute, 2023)
This study aims to examine, analyze and interpret; Effect of Supervision on performance improvement; The effect of discipline on increasing performance and the influence of motivation on increasing performance. This research is descriptive quantitative using a quantitative approach. The population and sample in this study amounted to 30 people. Methods Data collection was carried out by distributing questionnaires, interviews and literature study. This research was analyzed with the help of SPSS 24 software. The results showed that: 1) Supervision has a positive and significant effect on improving teacher performance. Supervision used by school principals plays a very important role in improving performance. its performance with a certain perspective; 2) Discipline has a positive and significant effect on improving teacher performance, with the application of discipline, teachers can carry out their duties as educators in a directed and timely manner which will then have a positive impact on the development of students; 3) Motivation has a positive and significant effect on improving teacher performance. The existence of internal and external motivation makes teachers have confidence and commitment and high awareness in carrying out their duties even without coercion from the leadership.